Hockey the NHL way. Hockey tips from the pros - Rossiter, Sean, 1946-; Carson, Paul, 1955- (Vancouver ; New York : Greystone Books, 2001)
Presents advice on developing the physical and mental skills required to succeed as a hockey player in the form of short quotations from National Hockey League players such as Dominik Hasek, Saku Koivu, and Mario Lemieux. Includes full-page color photographs.
Keywords: Hockey -- Juvenile literature; Hockey players -- Juvenile literature; Hockey; Hockey players